MQAM modulation scheme recognition using Hilbert transform - XI Jia-xi; WANG Zong-xin (Tongxin xuebao)
A modulation scheme recognition algorithm for MQAM signals was proposed.The method does not require the prior information about baud rate and carrier frequency of the received signals.Baud rate is estimated first,then re-sampling,Hilbert transformation,baud rate sampling and clustering are performed.It does not need carrier frequency estimation and decreases the calculation.Computer simulations show that the correct recognition ratio is larger than 95% if SNR is greater than 12dB and using 1024 or more symbols.So it is suitable for signal detection and recognition of practical applications.